Pengaruh Motivasi Ekstrinsik dan Motivasi Intrinsik terhadap Prestasi Belajar Siswa Mata Pelajaran Teknologi Perkantoran - Sembiring, Rani Sartika Br; Nura, Alfi (Jurnal Nasional Manajemen Pemasaran dan SDM, 2022)
The problem in this study is the low student achievement in office technology subjects and the low parental attention and learning motivation of class X OTKP students at SMK PAB 2 Helvetia for the 2021/2022 academic year. The purpose of this study was to determine the effect of extrinsic motivation (Parental Attention) and Intrinsic motivation (learning motivation) on learning achievement of class X office technology OTKP SMK PAB 2 Helvetia in the 2022/2022 academic year. This research is a population study where all students of class X OTKP SMK PAB 2 Helvetia which consists of 3 classes totaling 88 people and the sampling method in this study is total sampling. Data collection techniques in this study were observation, interviews, questionnaires, and documentation. The data analysis technique used is multiple linear regression analysis, to test the hypothesis using the t test and F test and the coefficient of determination (R2) with the help of the SPSS version 25 program. Based on the results of research and data processing, it can be seen that the regression equation Y = 12.621 + 0.402X1 + 0.433X2. From the results of the F test, it is found that Fcount > Ftable (71.421 > 3.10) with a research significance of 0.000 with a significant level of of 0.005 that the significance value of the study is smaller than the significance of = 0.005 (0.00 < 0.005). Based on this, the hypothesis is accepted so that it can be concluded that the variable has a positive and significant influence simultaneously between the variables of parental attention (X1) and learning motivation (X2) on the achievement of class X OTKP SMKS PAB 2 Helvetia students (Y). The coefficient of determination (R2) is 0.627 or 62.7%. This shows that the contribution of the independent variable to the dependent variable is 62.7% and the rest is influenced by other factors.